Responding to Food Price Crisis in Eastern and Southern Africa: Policy Options for National and Regional Action - Karugia, Joseph T.; Waithaka, M.M.; Freeman, H.A.; Prabhu, Ravi; Shiferaw, B.; Gbegbelegbe, Sika; Massawe, Stella C.; Kyotalimye, M.; Wanjiku, J.; Macharia, E. (International Food Policy Research Institute, 2009)
This paper addresses the magnitude and implications of food price changes in national and regional markets in Eastern and Southern Africa (ESA) with a view to provide the evidence base for effective policy action. Specifically, the paper: - analyses trends and outlooks in country and regional data, presents evidence on the regional food situation, and explores the nexus between high domestic food prices and global food prices, - highlights regional and national dimensions of food price increases and how they are related to food security in the region, and - provides practical short-, medium- and long-term options for governments and other stakeholders for addressing the problem posed by the food price crisis.